1991
DOI: 10.1007/bf00845456
|View full text |Cite
|
Sign up to set email alerts
|

Preventing relapse in obesity through posttreatment maintenance systems: Comparing the relative efficacy of two levels of therapist support

Abstract: The present study compared the relative effectiveness of a therapist-supported maintenance condition with a minimal contact maintenance condition in preventing relapse following an obesity treatment program. Thirty-two subjects who completed an initial 12-week cognitive/behavioral plus aerobic exercise treatment program were matched on absolute weight loss and randomly assigned to one of two maintenance conditions. Subjects were assessed at pretreatment, posttreatment, and 3, 6, and 12 months following posttre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 16 publications
0
37
0
Order By: Relevance
“…There is considerable data demonstrating that individuals who are successful at losing and maintaining their weight have more communication with their researcher than those who lose contact. [17][18][19][20][21] It seems unlikely, however, that simply communicating electronically via e-mail over the Internet was the distinguishing feature because the use of the Internet has been found to be no more effective at maintaining weight than direct contact. 22 Finally, it is possible that the students used the information provided to them by the TMS as an early indicator of a small error in their energy balance.…”
Section: Discussionmentioning
confidence: 99%
“…There is considerable data demonstrating that individuals who are successful at losing and maintaining their weight have more communication with their researcher than those who lose contact. [17][18][19][20][21] It seems unlikely, however, that simply communicating electronically via e-mail over the Internet was the distinguishing feature because the use of the Internet has been found to be no more effective at maintaining weight than direct contact. 22 Finally, it is possible that the students used the information provided to them by the TMS as an early indicator of a small error in their energy balance.…”
Section: Discussionmentioning
confidence: 99%
“…3,7,10 Lack of dietetic contact or ongoing intervention following the completion of the initial intervention has been shown to be less effective in producing continued weight loss or maintaining weight loss. 19,20 This study tried to mimic real clinical practice as much as possible. The pre-prepared meals and meal replacement were subsidised or provided free to subjects for the initial intervention, as has been the case with previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6] Little research has been carried out on the processes associated with weight regain, as opposed to successful weight maintenance, in obesity. Studies that have followed-up obese patients who have participated in treatment trials have suggested that relapse is attributable to individuals' failure to persist with the weight-control behaviours that they adopted to achieve weight loss, such as the consumption of a low-fat diet 7 ; regular physical activity [7][8][9][10] ; and the regular monitoring of body weight. 1,2,7,8,[11][12][13] Little attention has been paid to why this is the case and how some formerly obese individuals are able to persist with these forms of behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…Studies that have followed-up obese patients who have participated in treatment trials have suggested that relapse is attributable to individuals' failure to persist with the weight-control behaviours that they adopted to achieve weight loss, such as the consumption of a low-fat diet 7 ; regular physical activity [7][8][9][10] ; and the regular monitoring of body weight. 1,2,7,8,[11][12][13] Little attention has been paid to why this is the case and how some formerly obese individuals are able to persist with these forms of behaviour. 14 The findings of a small number of retrospective studies suggest that factors such as having unrealistic weight goals, [15][16][17] poor coping or problem-solving skills, 11,12,18,19 low self-efficacy, 7,11,15,20 and an imbalance between the effort involved and the benefits received from weight maintenance 21,22 may contribute.…”
Section: Introductionmentioning
confidence: 99%